Pendampingan Pengembangan Aplikasi Statistik Komoditi Berbasis Web pada Dinas Perkebunan Sumatera Selatan - Dzakwan, Fadhlur Rahman; Kunang, Yesi Novaria; Yadi, Ilman Zuhri; Afiyudi, Afiyudi (Jurnal Nasional Pengabdian Masyarakat, 2025)
This article discusses a community service program involving assistance in developing a web-based commodity statistical application at the South Sumatra Plantation Office. This activity aims to enhance data processing efficiency and disseminate information related to plantation commodities. This program involves training staff in the use of information technology and developing applications that meet user needs. The methodologies applied include needs analysis, system design, implementation, and application evaluation. The assistance results indicate a significant improvement in data accuracy and ease of information access, positively impacting policy decision-making in the plantation sector. This activity is expected to contribute to developing similar applications in other government agencies and encourage the use of technology in commodity data management.